Research on Stiffness Identification Method for Complex Joints Based on Modal Correlation Analysis - Ruijiang Yu; Shujuan Li; Lie Liang; Feilong Liu; Kaixuan Wang (Machines, 2022)
The dynamic performance of mechanical systems is seriously affected by the stiffness of mechanical joints. The tool holder system of the deep hole machine tool was taken as the object; based on the modal correlation of experiment and finite element simulation, a simple and practical method was proposed to obtain the joint stiffness of the tool holder system under the structure form of the tool overhang of 200 mm. For the same tool holder system, the simulation and experimental analysis were carried out with different structural forms of tool overhang of 300 and 400 mm, which further verified the correctness and feasibility of the method for obtaining the joint stiffness, as well as provided a new idea and certain theoretical basis for extracting the joint stiffness of the tool holder system in deep hole machining.